2021
DOI: 10.3390/antibiotics10010046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Berry Polyphenolic Fraction on Biofilm Formation, Adherence Properties and Gene Expression of Streptococcus mutans and Its Biocompatibility with Oral Epithelial Cells

Abstract: The ability of Streptococcus mutans to adhere to oral surfaces and form biofilm is a key step in the tooth decay process. The aim of this study was to investigate a berry (wild blueberry, cranberry, and strawberry) polyphenolic fraction, commercialized as Orophenol®, for its antibacterial, anti-biofilm, and anti-adhesion properties on S. mutans. Moreover, the biocompatibility of the fraction with human oral epithelial cells was assessed. Phenolic acids, flavonoids (flavonols, anthocyanins, flavan-3-ols), and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In a previous study [ 22 ], we showed that at concentrations up to 500 μg/ml, the berry polyphenolic fraction did not significantly decrease the oral keratinocyte (B11 cell line) viability in a colorimetric MTT test. Treating the oral keratinocytes with P. gingivalis (MOI of 10 3 ) up-regulated ROS production by 2.3-fold ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In a previous study [ 22 ], we showed that at concentrations up to 500 μg/ml, the berry polyphenolic fraction did not significantly decrease the oral keratinocyte (B11 cell line) viability in a colorimetric MTT test. Treating the oral keratinocytes with P. gingivalis (MOI of 10 3 ) up-regulated ROS production by 2.3-fold ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 90%
“…A stock solution was prepared in distilled water at a concentration of 10 mg/ml, was filter-sterilized (0.2-μm pore size membrane filter), and was kept at 4°C under darkness for up to 1 month. The phenolic content of the preparation was analyzed by chromatographic and mass spectrometry techniques and has been detailed in a previous study [ 22 ]. In brief, phenolic acids, flavonoids (flavonols, anthocyanins, flavan-3-ols), and procyanidins made up 10.71, 19.76, and 5.29% (w/w) of the berry polyphenolic preparation, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The growing concerns of the side effects produced by the use of traditional antibacterial agents such as chlorhexidine and fluoride for the prevention of dental caries caused by S. mutans has shifted the public attention to natural products (Singla et al 2018 ; Souissi et al 2021 ; Vijayakumar et al 2021 ). As an example, baicalein, a flavonoid isolated from the roots of Scutellaria baicalensis and Scutellaria lateriflora , is capable of inhibiting the biofilm formation, acid production, and cell surface hydrophobicity in S. mutans while without inhibiting its growth (Vijayakumar et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…S. mutans is capable of metabolizing the dietary carbohydrates to produce diverse organic acids that induce the demineralization of enamel, resulting in the progression of dental caries (Vijayakumar et al 2021 ). Furthermore, the robust ability to form biofilm and adapt to stressful conditions during host colonization enables S. mutans to adhere enduringly to the tooth surface and escape from elimination by general oral cleaning and care (Souissi et al 2021 ; Priya et al 2021 ). Therefore, inhibiting the biofilm formation of S. mutans is one important way for preventing dental caries development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation